Cross-sectional correlational study on Patient Satisfaction with Total Quality Management in Saudi Arabia's Healthcare Industry - al madani, khayreya; Alsulami, Rawan Muhji; Almaghrabi, Rasha Ahmad; Banjar, HEBA Raslan Sabran; Natto, Abrar Mohammad O; Albarakati, Nawal Zamil Hamzah; Dignah, Daniah; gousti, Naglaa Yakoub; Alghamdi, Abdullah Saad; Alqahtani, Adel Saeed; Alahmadi, Alaa Omar; Albeshi, Hend Sarhana; et al. (Journal of Ecohumanism, 2024)
Over the last decade, healthcare organizations worldwide have faced many challenges mainly concerned with their services' efficiency, effectiveness, and quality. There has been a pressing need for healthcare organizations to embrace or adopt new approaches to managing the quality of services to enhance patient satisfaction. Quality management plays a role in determining healthcare outcomes and patient satisfaction in hospitals. Aim: to examine the connection between total quality management (TQM) and patient satisfaction (PSAT). Methodology: a quantitative cross-sectional correlational study, a convenience sample of 320 in-patients receiving treatment at a governmental hospital, Alnoor Hospital in Saudi Arabia. Data was collected using two questionnaires: total quality management (TQM) and patient satisfaction (PSAT) with data analysis conducted using SPSS26. Conclusion: The findings revealed that total quality management positively influenced patient satisfaction. Limitation: Since there are fewer studies on total quality management in the healthcare sector than in manufacturing industries, this research makes a substantial contribution to the body of literature already in existence and merits additional study. Furthermore, this research offers significant perspectives for managers in the healthcare industry about strategic planning and decision-making procedures.